Respuesta :

raz00r

Answer: C. [tex]f(n) = -4(-3)^{n-1}[/tex]

Step-by-step explanation: The formula for a geometric sequence is [tex]ar^{n-1}[/tex], where a = first term in the sequence

r = common ratio

n = position of term

Here they already told us a = -4, so we have to figure out r. We can see that in the sequence -4, 12, -36, 108... the terms are being multiplied by -3, which is why the negative and positive terms alternate.

Therefore, the formula is: [tex]f(n) = -4(-3)^{n-1}[/tex]

You can try inserting n to check it.

[tex]f(1) = -4(-3)^{1-1} = -4\\f(2) = -4(-3)^{2-1} = 12\\f(3) = -4(-3)^{3-1} = -36\\f(4) = -4(-3)^{4-1} = 108[/tex]

Option C

Let's verify

  • f(1)=-4(-3)^0=-4
  • f(2)=-4(-3)^1=12
  • f(3)=-4(-3)^2=-36

Hence verified